2021
DOI: 10.36519/kd.2021.11
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of COVID-19 Cases in A University Hospital in Turkey

Abstract: Objective: It is important to put forward the characteristics of the COVID-19 cases to fight the disease effectively. The aim of this study is to determine the epidemiological characteristics of COVID-19 cases in Turkey. And also to determine the risk factors associated with intensive care unit (ICU) admission and death. Methods: In this cross-sectional study, the characteristics of the confirmed COVID-19 cases who applied to a University Hospital in Turkey between March 19th and June 11th, 2020, were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…However, the follow-up rate in the intensive care unit of our current study population is 93.8% (n=75), and the mortality rate reported in the literature for patients who need follow-up in the intensive care is around 50% (21,22). In a study published in Turkey, on the other hand, this rate was reported as 78% (23). The mortality rate observed for the E a r l y A c c e s s patients who underwent TPE was 75.0% (n=60) on the 28 th day of the procedure in our study, and this rate is similar to the cases in which the procedure was not performed compared to the literature.…”
Section: Discussionmentioning
confidence: 55%
“…However, the follow-up rate in the intensive care unit of our current study population is 93.8% (n=75), and the mortality rate reported in the literature for patients who need follow-up in the intensive care is around 50% (21,22). In a study published in Turkey, on the other hand, this rate was reported as 78% (23). The mortality rate observed for the E a r l y A c c e s s patients who underwent TPE was 75.0% (n=60) on the 28 th day of the procedure in our study, and this rate is similar to the cases in which the procedure was not performed compared to the literature.…”
Section: Discussionmentioning
confidence: 55%
“…In a meta-analysis study involving 8,088 patients diagnosed with COVID-19, it was reported that patients aged 65 and over had higher rates of intensive care admission [23]. Teker et al (2021) stated that the course of COVID-19 disease gets worse with age and deaths increase [24]. Wang et al (2020) reported that the elderly are at higher risk for chronic diseases and infections and that mortality due to COVID-19 increases in those with hy-pertension and coronary heart disease [15].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies conducted in Turkey have reported that the majority of patients with COVID-19 are males and of an older age. Healthcare workers are also at a higher risk of contracting COVID-19 ( 6 , 7 ). This result has been attributed to the fact that ACE2 receptor expression is high in males; moreover, males lack estrogen and chromosome X protection ( 8 ).…”
Section: Discussionmentioning
confidence: 99%